Effectiveness of the MentalCare Website in Addressing Depression Among Failed Legislative Candidates in Ambon City, Maluku Province - Ismail Mamang; Ahmed Yussof; Luh Putu Vera Astri Pujayanti; Muhammad Suhardi (International Journal of Scientific Research, 2024)
Elections are a fundamental mechanism of democracy, granting citizens the right to select leaders or representatives who will advocate for their interests and aspirations in political decision-making. Achieving electoral victory and securing a legislative position is the ultimate goal for all candidates. However, legislative candidates who face defeat, especially after significant financial investments, may struggle to cope with the harsh reality of failure. This increases their vulnerability to stress and even severe depression. While the provision of hospital facilities for failed candidates has been attempted, concerns over misuse render it less effective. Therefore, an alternative approach is needed, such as utilizing the MentalCare website to mitigate depression among unsuccessful legislative candidates. This study aims to evaluate the effectiveness of the MentalCare website in addressing depression among failed legislative candidates in Ambon City. Using a qualitative descriptive research method, the findings reveal that the MentalCare website demonstrates significant potential in positively impacting mental health, particularly in managing depression among candidates who experienced electoral failure. By overcoming existing barriers and continually improving service quality, the MentalCare website can emerge as an effective and sustainable solution for promoting individual and community mental well-being.